2012
DOI: 10.1371/journal.pone.0049111
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Prevalence in Tuberculosis Patients in Germany, 2002–2009: An Estimation Based on HIV and Tuberculosis Surveillance Data

Abstract: Tuberculosis (TB) and HIV comorbidity is a major challenge in TB prevention and control but difficult to assess in Germany as in other countries, where data confidentiality precludes notifying the HIV status of TB patients. We aimed to estimate the HIV-prevalence in TB patients in Germany, 2002–2009, and to characterize the HIV/TB patients demographically. Data from the long-term observational open multicentre cohort ClinSurv HIV were used to identify incident TB in HIV-positive individuals. We assessed the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 22 publications
2
5
0
1
Order By: Relevance
“…Regarding sociodemographic characteristics, this study confirmed the results of previous research [27,28]. The profile of the co-infected individual is a white males with a low level of education and a mean age of 38 ± 9,91 years.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding sociodemographic characteristics, this study confirmed the results of previous research [27,28]. The profile of the co-infected individual is a white males with a low level of education and a mean age of 38 ± 9,91 years.…”
Section: Discussionsupporting
confidence: 90%
“…To every TB patient HIV diagnostics should be offered since HIV co-infection may present particular problems. 2,10,16 To our initial surprise TB was recognized earlier in HIV+ patients analogous to an observation confirmed by two recent studies from the UK. 22,23 Explanations may be that in HIV+ patients infectious diseases are considered earlier, that the treating doctor is experienced with infectious diseases, that paucibacillary cases are less frequent, that consequently PCR less frequently yield false negative results, that the clinical course is more acute, and that pulmonary manifestations are more common.…”
Section: Discussionsupporting
confidence: 75%
“…This anticipates an increase of both TB and HIV patients in immigrants to Germany. 1,3,9–13 Furthermore, extrapulmonary TB, which appears to affect more often in female patients, might also increase. 14 Both infections, TB and HIV, need to be recognized early, to avoid further spread to the population and mismanagement of the individual patient.…”
Section: Discussionmentioning
confidence: 99%
“…Our study aimed to investigate the frequency of tuberculosis in subpopulations, but it does not allow for estimating risk at the individual level given that individuals may be heterogeneous in terms of other risk factors for tuberculosis, e.g. socio-economic determinants, risk behaviour such as smoking and alcohol or drug abuse, or HIV co-infection [ 33 ]. Further, sample size did not allow us to stratify the rate of tuberculosis in immigrants by different countries or areas of origin.…”
Section: Discussionmentioning
confidence: 99%